2022
DOI: 10.1161/jaha.121.026472
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Geographic Access to Cardiac Rehabilitation in Los Angeles County

Abstract: Background Exercise‐based cardiac rehabilitation (CR) is known to reduce morbidity and mortality for patients with cardiac conditions. Sociodemographic disparities in accessing CR persist and could be related to the distance between where patients live and where CR facilities are located. Our objective is to determine the association between sociodemographic characteristics and geographic proximity to CR facilities. Methods and Results We identified act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The lack of data in some regions and the variability of healthcare systems between the areas limit the generalizability of the results. 61 , 62 …”
Section: Discussionmentioning
confidence: 99%
“…The lack of data in some regions and the variability of healthcare systems between the areas limit the generalizability of the results. 61 , 62 …”
Section: Discussionmentioning
confidence: 99%
“…These findings are in line with a study of Los Angeles residents showing that racial/ethnic minority groups were more likely to have CR facilities 5 or more miles away relative to their white counterparts. 15 However, it is unclear if the increased distance is associated with decreased utilization, as prior studies have shown that distances over 30 miles are linked to lower rates of use. 25 Interventions focused on improving CR access may, therefore, need to be tailored based on whether CR facilities are in close proximity to patients.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Patients in lowerincome neighborhoods may also have lower rates of CR participation because of limited access to CR facilities. 15 Over and above the established predictors of participation in CR, none of the above studies have evaluated the independent relationship between community-level distress and CR participation at a national level. Moreover, there is limited evidence of an association between CR participation and outcomes across levels of community distress.…”
mentioning
confidence: 99%
“…Prior studies have shown disparities in access to key resources such as COVID-19 vaccination sites, pediatric trauma centers, dialysis units and cardiac rehabilitation centers [13,[40][41][42]. It is clear from this data that critical care resources are also not equitably available to all areas and populations of the US.…”
Section: Plos Onementioning
confidence: 92%